Office Window Security Monitoring System Based on The Internet of Things (IoT) in Unwaha - Siti Sufaidah; Muhyiddin Zainul Arifin; Isyatir Rodliyah Mahmudah; Sujono Sujono (NEWTON: Networking and Information Technology, 2022)
Currently, the crime rate in the office environment is increasing for both types of crime and other crimes. Then a security system is needed to maintain office security. Security systems using IoT are an option that many people are interested in. Therefore, this study aims to help employees know the condition of window security, which can be monitored from anywhere. The system is monitored using the NodeMCU microcontroller and Magnetic Sensor, and the blynk application, which can then be used as a tool to find out whether all windows have been closed or not. conditions if the window is open or closed.